(untitled) (Bangladesh Journal of Urology, 2020)
A 45 years old male, nondiabetic, hypertensive, nonasthmatic, nonsmoker, farmer from Pabna presented with the complaints of pain over right hypochondrium for 4 months andalso gave history of significant weight loss of about 15 kg in the last 6 months. He also developed bilateral gynecomastia for 2 years.On examination, Blood pressure was 200/100 mm of Hg and bilateral gynecomastia were present.Both testes were mildly atrophied.Systemicexamination revealed mild tenderness in right hypochondrium on deep palpation of abdomen.USG of W/A revealed A heterogenous mixed echogenic mass (9.9*8.9) was seen in upper polar region of right kidney. Suggestive of Right suprarenal mass. CT scan W/A with contrast showed heterogenous contrast enhancing well defined rounded soft tissue density lesion measuring about 90*86 mm was noted in right adrenal region which revealed a right adrenal mass consistent with adrenal pheochromocytoma. However,clinical biochemistry tests revealed normal levels of plasma catecholamines (dopamine,norepinephrine, and epinephrine) and metanephrine, which are unusual findings in adrenal pheochromocytoma.Serum Aldosterone,Basal cortisol, Renin in plasma, ACTH and 24 hours Urinary Free cortisol were normal.Meanwhile, The patient had persistent hypokalemia and serum Testosterone, LH and FSH were below normal level. Open right adrenalectomy was done. Histopathology and immunohistochemistryconfirmed the diagnosis of adrenal pheochromocytoma. Following surgery, the patient did well and showed full recovery at follow-up after one month. To our knowledge, this is the first report in Dhaka Medical college hospital of the extremely rare entity of pheochromocytoma with an unusual clinical and biochemical scenario. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.168-171